Academic Portal with MFA (WhatsApp OTP via Fonnte), Role-Based Access Control, and Logging System for Network Monitoring - Manik, Albert Ramadhan; Kiswanto, Dedy; Akbar, Muhammad Budi; Purba, Jogi (Jurnal Ilmiah Sistem Informasi, 2025)
This study aims to develop a web-based academic portal with a multi-layered security system to enhance data protection and operational efficiency. The system integrates Multi-Factor Authentication (MFA) using WhatsApp OTP via Fonnte, Role-Based Access Control (RBAC), and a user activity logging mechanism to ensure security, transparency, and accountability. Additionally, a web-based security monitoring feature is implemented, allowing administrators to observe user activities in real-time and respond promptly to potential threats. The testing results indicate that the combination of MFA, RBAC, and logging effectively strengthens the system against unauthorized access while improving its stability and reliability. Therefore, the developed system proves to be an effective solution for securing academic data, minimizing security risks, and optimizing the management of educational information.